Community Empowerment: Strengthening the Capacity of Bumdes Management "Sidorejo Makmur" - Kustaji; Muhammad Rizqi Agustino; Fauzian Noor; Reza Anggapratama; Dwi Irnawati; Mugito; Budianto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The existence of (BUMDesa) "Sidorejo Makmur" belonging to the Sidorejo Village Government, Sukosewu District, Bojonegoro Regency, is expected to be able to strive for, strengthen, and improve the economy in the village. However, this institution still faces various problems, especially regarding management capacity. The management's managerial abilities are still far from the expectations of business entity management standards. Management still receives minimal training in planning business activities, administration of business entities and management and supervision of a business entity. The inability and fear of taking steps still occurs among all administrators, who are still new players, so innovative ideas are still dry and stuck on old businesses running in BUMDesa business units that have existed for a long time. This service and empowerment seek to strengthen administrators' capacity to increase their capacity in managing business management and finding various solutions for the progress and development of BUMDesa. So that the objectives of the activity are carried out and achieved well, mentoring also involves students starting from socialization of activities, and simple management training, strengthening management capacity, administrative management, and strengthening opportunities for developing business potential so that BUMDesa administrators can carry out their functions optimally, manage BUMDes, control and regulate activities a business that is managed and can be held accountable for activities to all stakeholders, the end of which will be the prosperity of the village community.